Hospitalisations from birth to 5 years in a population cohort of Western Australian children with intellectual disability. Issue 12 (21st November 2005) - Williams, K; Leonard, H; Tursan d'Espaignet, E; Colvin, L; Slack-Smith, L; Stanley, F
Abstract : Aims: To describe the hospitalisation history in the first five years of life for all children born in Western Australia (WA) between 1983 and 1992 and diagnosed with intellectual disability (ID). Methods: Unit record linkage of the WA Midwives Collection, WA Intellectual Disability Database, and the WA Hospital Morbidity Dataset provided the population database of WA born children with and without ID. Affected children were divided into those co-affected with autism spectrum disorders (ASD), and those whose ID had or had no known biomedical cause. Those without a biomedical cause were further subdivided into mild–moderate and severe categories. Results: On average, ID affected children were more likely than non-affected children to be admitted to hospital (RR: 1.64; 95% CI 1.6 to 1.7), on more occasions (5.3 versus 2.2 admissions), for longer (29.6 versus 8.3 days), and for a larger range of clinical diagnoses. The only exception was the group of children co-diagnosed with ASD whose hospitalisation profile resembled more that of non-affected children. Conclusions: This total population study is unique because of the availability of the system of linkable population registers and administrative health databases in WA. The results indicated that this vulnerable population of children with ID has substantial medical needs. This paper points to the need for authorities to develop supportive programmes for this population especially in the current climate of de-medicalisation of ID. More research is not only needed on the welfare of the affected children but also on the impact of the substantial medical and other needs of affected children on the rest of their immediate and extended families.